Fauna silvestre que afecta los cultivos en Boyacá y control del daño a cultivos de maíz - Castillo López, Israel Fernando; Rodríguez Africano, Pablo Emilio; Montes Pérez, Rubén Cornelio; González Valderrama, Diana Milena (Universidad Pedagógica y Tecnológica de Colombia, 2017)
Páginas 75-84